Positive electrode active material precursor for secondary battery, positive electrode active material, preparation method thereof, and lithium secondary battery containing the positive electrode active material

By controlling the crystal structure orientation in the precursor of the positive electrode active material of the lithium secondary battery, reducing the area exposed to the lithium moving path of the (003) plane, the problem of deterioration of the capacity and output characteristics of the positive electrode active material of the lithium secondary battery is solved, and a higher lithium mobility and performance improvement is achieved.

CN114728811BActive Publication Date: 2025-04-29LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180006089.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-29
Filing Date
2021-01-29
Publication Date
2025-04-29
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

When the positive electrode active material of the existing lithium secondary battery is embedded/de-embedded, the (003) plane is exposed to the lithium moving path, resulting in deterioration of capacity and output characteristics.

Method used

By controlling the crystal structure orientation of the precursor of the positive electrode active material, the long axis of the primary particle is arranged in a direction from the center of the secondary particle toward the surface, and the (001) surface is not parallel to the long axis direction of the primary particle at an angle of 20° to 160°, thereby reducing the exposed area of ​​the (003) surface.

Benefits of technology

The mobility of lithium is improved, capacity characteristics and output characteristics are improved, and the performance of the positive electrode active material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114728811B_ABST
    Figure CN114728811B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material precursor for a secondary battery and a method for preparing the same, wherein the positive electrode active material precursor of the present invention is in the form of a secondary particle in which a plurality of primary particles are aggregated, wherein the major axis of the primary particle is arranged in a direction from the center of the secondary particle toward its surface, wherein the primary particle comprises a crystal grain in which a (001) plane is arranged in a direction having an angle of 20° to 160° relative to the major axis direction of the primary particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority from Korean Patent Application No. 10-2020-0010701, filed on January 29, 2020, the disclosure of which is incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material precursor for a secondary battery, a positive electrode active material, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. Background Art

[0003] Recently, with the rapid popularization of electronic devices such as mobile phones, notebook computers and electric vehicles using batteries, the demand for secondary batteries with relatively high capacity, small size and light weight has increased dramatically. In particular, because lithium secondary batteries are light in weight and have high energy density, lithium secondary batteries have become the focus as driving power sources for portable devices. Therefore, research and development attempts have been actively carried out to improve the performance of lithium secondary batteries.

[0004] In a lithium secondary battery in which an organic electrolyte or a polymer electrolyte is filled between a positive electrode and a negative electrode (the positive electrode and the negative electrode are respectively formed of active materials capable of inserting and deinserting lithium ions), electric energy is generated by oxidation and reduction reactions when lithium ions are inserted into or deinserted from the positive electrode and the negative electrode.

[0005] As the positive electrode active material of lithium secondary batteries, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.) or lithium iron phosphate compounds (LiFePO4) have been used. Among them, lithium cobalt oxide (LiCoO2) is widely used because of its high operating voltage and excellent capacity characteristics, and has been used as a positive electrode active material for high voltage. However, because the price of cobalt (Co) has risen and the supply is unstable, the large-scale use of lithium cobalt oxide as a power source for applications such as electric vehicles is limited, and it is necessary to develop a positive electrode active material that can replace the lithium cobalt oxide.

[0006] Therefore, a nickel-cobalt-manganese-based lithium composite transition metal oxide (hereinafter referred to as "NCM-based lithium composite transition metal oxide") has been developed in which a part of cobalt (Co) is replaced by nickel (Ni) and manganese (Mn).

[0007] Typically, NCM-type positive active material precursors are synthesized by coprecipitation, wherein the shape of the precursor primary particles is formed differently according to the coprecipitation conditions. In the case of using a precursor having a spherical or cubic shape of primary particles to prepare a positive active material, the primary particles of the positive active material are also formed into a spherical or cubic shape, wherein in this case, the movement path of lithium is increased to reduce the mobility of lithium. Therefore, a technique has been developed to synthesize the shape of the primary particles of the precursor into a shape such as a rod or column. In the case where the shape of the precursor primary particles is rod-shaped or columnar, the primary particles are formed in a radial arrangement from the center of the secondary particles toward the surface direction, and in the case of preparing a positive active material by using a precursor having such a primary particle arrangement, because the distance that lithium ions move along the interface between the primary particles is reduced, the effect of improving lithium mobility can be obtained. However, for conventional positive active materials formed in a manner in which primary particles have a radial arrangement, because it is impossible to embed / de-embed the (003) face of lithium in a manner parallel to the long axis direction of the primary particles, there is a limitation on the degradation of capacity or output characteristics.

[0008] Therefore, there is a need to develop a positive electrode active material precursor and a positive electrode active material having an orientation that can exhibit excellent discharge capacity and output characteristics when used in a lithium secondary battery.

[0009] Prior art literature

[0010] (Patent Document 1) Korean Patent Application Publication No. 2013-0138073 Summary of the invention

[0011] Technical issues

[0012] One aspect of the present invention provides a cathode active material precursor and a method for preparing the same, wherein the orientation of the crystal structure of primary particles is specifically controlled at the cathode active material precursor stage.

[0013] Another aspect of the present invention provides a positive electrode active material prepared by using a precursor in which an orientation of a crystal structure is controlled, and a lithium secondary battery including the same.

[0014] Technical Solution

[0015] According to one aspect of the present invention, a positive electrode active material precursor for a secondary battery is provided, wherein the positive electrode active material precursor is in the form of secondary particles in which multiple primary particles are aggregated, wherein the long axis of the primary particle is arranged in a direction from the center of the secondary particle toward the surface of the secondary particle, wherein the primary particle contains grains, wherein the (001) plane is arranged in a direction having an angle of 20° to 160° relative to the long axis direction of the primary particle.

[0016] According to another aspect of the present invention, a method for preparing a positive electrode active material precursor for a secondary battery is provided, the method comprising: while adding a transition metal-containing solution containing cations of nickel (Ni), cobalt (Co) and manganese (Mn), an aluminum-containing solution containing cations of aluminum (Al), an alkaline aqueous solution and an ammonium solution to a reactor, forming a positive electrode active material precursor by a coprecipitation reaction, wherein the aluminum-containing solution contains sodium aluminate (NaAlO2).

[0017] According to another aspect of the present invention, a positive electrode active material for a secondary battery is provided, wherein the positive electrode active material is in the form of secondary particles in which multiple primary particles are aggregated, wherein the long axis of the primary particle is arranged in a direction from the center of the secondary particle toward its surface, wherein the primary particle contains grains, wherein the (003) plane is arranged in a direction having an angle of 20° to 160° relative to the long axis direction of the primary particle.

[0018] According to another aspect of the present invention, a positive electrode and a lithium secondary battery including the positive electrode active material are provided.

[0019] Beneficial Effects

[0020] In the positive electrode active material precursor according to the present invention, since the (001) plane of the grain is not formed in a manner parallel to the long axis direction of the primary particle but is formed in a manner deviated from the long axis direction, when a positive electrode active material is prepared by using the positive electrode active material precursor, the contact area between the interface of the primary particle as a lithium movement path and the (003) plane in which lithium is unlikely to be intercalated / deintercalated is reduced.

[0021] Thus, the cathode active material prepared by using the cathode active material precursor of the present invention has better lithium mobility than conventional cathode active materials, and can obtain the effects of improving capacity characteristics and output characteristics when the cathode active material is used in a lithium secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is a cross-sectional scanning transmission electron microscope (STEM) image of a conventional positive electrode active material, in which the (003) plane is formed in a direction parallel to the long axis of the primary particle. The arrow in the figure indicates the (003) plane direction. Figure 1 The image on the upper left is a STEM-EDX (energy dispersive X-ray) mapping image;

[0023] Figure 2 is a crystal structure of a primary particle of a positive electrode active material precursor according to one embodiment of the present invention and a graph showing changes in the surface area ratio of the (001) plane as a function of the aspect ratio of the primary particle;

[0024] Figure 3 : is a cross-sectional scanning transmission electron microscope (STEM) image of a positive electrode active material according to one embodiment of the present invention. In the figure, the short arrow indicates the (003) plane direction, and the long arrow indicates the long axis direction of the primary particle. As shown in the figure, in the positive electrode active material according to the present invention, the (003) plane is arranged in a manner not parallel to the long axis of the primary particle, but arranged in a manner having an angle of 20° to 160°. Figure 3 The image on the upper left is a STEM-EDX (energy dispersive X-ray) mapping image;

[0025] Figure 4 is a cross-sectional TEM image of the positive electrode active material precursor prepared in Example 1;

[0026] Figure 5 : are graphs showing the capacity and output characteristics of lithium secondary batteries using the positive electrode active materials prepared in Example 2 and Comparative Examples 3 and 4, respectively. DETAILED DESCRIPTION

[0027] Hereinafter, the present invention will be described in more detail to make the present invention more clearly understood. In this case, it will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in the commonly used dictionaries, and it will be further understood that the words or terms should be interpreted as having a meaning consistent with their meanings in the relevant technical field background and technical concept of the present invention on the basis that the inventor can appropriately define the meanings of the words or terms to explain the principles of the present invention in the best way.

[0028] In the present invention, the expression "grain" refers to a single crystal unit having a regular atomic arrangement, and the grain structure of the positive electrode active material precursor and the positive electrode active material can be confirmed by transmission electron microscopy (TEM / STEM) analysis.

[0029] In the present invention, the expression "primary particle" refers to the smallest particle unit that is distinguished as a piece when observing the cross section of the positive electrode active material particle or the positive electrode active material precursor particle by scanning transmission electron microscopy (STEM), wherein it can be composed of a single crystal grain, or it can also be composed of a plurality of crystal grains. In the present invention, the average particle size of the primary particles can be measured by measuring the size of each particle different from the cross-sectional STEM image of the positive electrode active material particle and calculating the arithmetic mean thereof.

[0030] In the present invention, the expression "secondary particles" refers to a secondary structure formed by aggregation of a plurality of primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer, and in the present invention, Microtrac S3500 is used as the particle size analyzer.

[0031] The expression "particle size D" of the positive electrode active material in the present invention is n " refers to the particle size at n% according to the volume cumulative distribution of particle sizes. That is, D 50 is the particle size at which 50% of the volume cumulative distribution of particle sizes is located, D 90 is the particle size at 90% of the volume cumulative distribution of particle sizes, and D 10 D is the particle size at which 10% of the volume cumulative distribution of particle sizes is found. n The measurement can be performed by using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium (distilled water), the dispersion medium is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in the diffraction pattern caused by the particle size when the particles pass through the laser beam. The particle size distribution can be measured by using a measuring instrument to calculate the particle size at 10%, 50%, and 90% of the volume cumulative distribution according to the particle size. 10 , D 50 and D 90 .

[0032] Hereinafter, the present invention will be described in detail.

[0033] <Positive electrode active material precursor>

[0034] The positive electrode active material precursor according to the present invention is characterized in that it is a positive electrode active material precursor in the form of secondary particles in which multiple primary particles are aggregated, wherein in this case, the long axis of the primary particle is arranged in a direction from the center of the secondary particle toward its surface, wherein the primary particle contains grains in which the (001) plane is arranged in a direction having an angle of 20° to 160° relative to the long axis direction of the primary particle.

[0035] A conventional positive electrode active material precursor is prepared in a form in which spherical primary particles are randomly arranged without orientation. In the case of preparing a positive electrode active material using a positive electrode active material precursor having a structure in which primary particles are randomly arranged without orientation as described above, the primary particles of the positive electrode active material also exist in an unaligned form. Because lithium ions move along the interface between the primary particles in the positive electrode active material particles, when the primary particles are randomly arranged in the positive electrode active material particles, the lithium movement path between the primary particles (inside the particles) increases, thereby causing a problem of deterioration of the output characteristics.

[0036] To solve this problem, the following have been developed: Figure 1 The positive electrode active material precursor shown has the following structure: the primary particles in the form of rods or columns are arranged radially from the center of the secondary particles to the surface direction. In the case of preparing the positive electrode active material using the positive electrode active material precursor in which the primary particles are arranged radially as described above, the primary particles of the positive electrode active material also remain radially arranged, so the lithium movement path between the primary particles can be minimized to obtain the effect of improving the lithium mobility. However, for the positive electrode active materials developed so far, the (001) face of the precursor grows parallel to the long axis direction of the primary particle. Because the (001) face of the precursor is transformed into the (003) face of the positive electrode active material after sintering, the (003) face of the positive electrode active material is arranged parallel to the long axis direction of the primary particle when the positive electrode active material is prepared using the precursor. Because the (003) face of the positive electrode active material is a face that is impossible to embed / de-embed lithium ions, there is a problem in that the capacity characteristics and output characteristics deteriorate when the area of ​​the (003) face exposed to the lithium movement path is large.

[0037] In order to improve this problem, in the present invention, because the long axis of the primary particle is arranged in the direction from the center of the secondary particle toward its surface, but the (001) plane of the grain in the primary particle is formed in a manner that is not parallel to the long axis direction of the primary particle, the area of ​​the (001) plane exposed under the interface of the primary particle is minimized to improve the capacity, charge and discharge efficiency and output characteristics.

[0038] Specifically, in the positive electrode active material precursor according to the present invention, the primary particles include grains in which the (001) plane is arranged in a direction that is not parallel to the long axis direction of the primary particles, and more specifically include grains in which the (001) plane is arranged in a direction having an angle of 20° to 160°, for example, 40° to 140°, relative to the long axis direction of the primary particles.

[0039] The precursor of the positive electrode active material of the present invention may be composed of a hydroxide containing nickel (Ni), cobalt (Co), manganese (Mn), and aluminum (Al). Preferably, the precursor of the positive electrode active material may contain aluminum (Al) at a concentration of 1 mol% or more relative to all metal elements, and more preferably may contain aluminum (Al) at a concentration of 1 mol% to 10 mol%. When the content of aluminum (Al) is within the above concentration range, the disordering of cations and the formation of oxygen vacancies can be suppressed.

[0040] Aluminum (Al) can be contained at a constant concentration in the secondary particles without a concentration gradient, that is, under the condition independent of the position within the particles. Since aluminum (Al) is distributed at a constant concentration and there is no concentration gradient in the secondary particles, the agglomeration phenomenon of aluminum (Al) can be suppressed, thereby minimizing the reduction of capacity and improving the effects of improving the life characteristics and the resistance increase rate characteristics with a small amount of aluminum (Al).

[0041] Preferably, the precursor of the positive electrode active material according to the present invention may be a transition metal hydroxide represented by the following formula 1.

[0042] [Formula 1]

[0043] Ni x1 Co y1 Mn z1 Al s1 (OH)2

[0044] In formula 1, x1 represents the molar ratio of nickel relative to all metal elements in the transition metal hydroxide, where x1 may satisfy 0.7 ≤ x1 ≤ 0.99, 0.8 ≤ x1 ≤ 0.99, 0.85 ≤ x1 ≤ 0.99, or 0.88 ≤ x1 ≤ 0.99.

[0045] y1 represents the molar ratio of cobalt relative to all metal elements in the transition metal hydroxide, where y1 may satisfy 0 < y1 < 0.3, 0 < y1 < 0.2, 0 < y1 < 0.15, or 0 < y1 < 0.12.

[0046] z1 represents the molar ratio of manganese relative to all metal elements in the transition metal hydroxide, where z1 may satisfy 0 < z1 < 0.3, 0 < z1 < 0.2, 0 < z1 < 0.15, or 0 < z1 < 0.12.

[0047] s1 represents the molar ratio of aluminum relative to all metal elements in the transition metal hydroxide, where s1 may satisfy 0.01 ≤ s1 ≤ 0.1, 0.01 ≤ s1 ≤ 0.08, or 0.01 ≤ s1 ≤ 0.05.

[0048] The primary particles of the positive electrode active material precursor may be in a columnar shape, and in this case, the aspect ratio of the primary particles may be 3 or more. More preferably, the aspect ratio of the primary particles of the positive electrode active material precursor may be in the range of 3 to 15, for example, 5 to 8. When the aspect ratio of the primary particles of the positive electrode active material precursor satisfies the above range, since the surface area of ​​the crystal plane where lithium can be intercalated / deintercalated increases at the interface between the primary particles as a lithium movement path, a positive electrode active material having excellent capacity and output characteristics can be prepared.

[0049] exist Figure 2 , there is shown a grain structure of a positive electrode active material precursor according to an embodiment of the present invention and a graph showing the variation of the surface area ratio of the (001) plane and the crystal plane with the aspect ratio, wherein the embedding / de-embedding of lithium ions on the outer surface of the primary particle is possible in the crystal plane.

[0050] like Figure 2 As shown, in the positive electrode active material precursor according to the present invention, the (001) plane is arranged in a direction (e.g., a vertical direction) that is not parallel to the growth direction of the crystal structure (the long axis direction of the primary particle), and therefore, the area of ​​the crystal planes other than the (001) plane exposed to the interface between the primary particles is wider than that of the conventional positive electrode active material precursor. In addition, as the aspect ratio of the primary particles increases, the proportion of the crystal planes other than the (001) plane exposed to the outer surface of the primary particles increases. Thus, in the case of preparing a positive electrode active material by using a positive electrode active material precursor as described above, because the surface area of ​​the (003) surface exposed to the outer surface of the primary particles can be minimized, the capacity and output characteristics can be improved.

[0051] Next, the method for preparing a positive electrode active material precursor of the present invention will be described.

[0052] The positive electrode active material precursor of the present invention is formed by adding a transition metal solution containing cations of nickel (Ni), cobalt (Co) and manganese (Mn), an aluminum solution containing cations of aluminum (Al), an alkaline aqueous solution and an ammonium solution to a reactor through a co-precipitation reaction, wherein the aluminum solution is prepared by including sodium aluminate (NaAlO2).

[0053] The method of preparing the positive electrode active material precursor will be described in detail with respect to each step.

[0054] First, a cathode active material precursor is prepared by a coprecipitation reaction while adding a transition metal-containing solution containing cations of nickel (Ni), cobalt (Co) and manganese (Mn), an aluminum-containing solution containing cations of aluminum (Al), an alkaline aqueous solution and an ammonium solution into a reactor.

[0055] The transition metal-containing solution may include, for example, a nickel (Ni)-containing raw material, a cobalt (Co)-containing raw material, and a manganese (Mn)-containing raw material.

[0056] The nickel (Ni)-containing raw material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxyl, and may specifically be Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt, nickel halide or a combination thereof, but the present invention is not limited thereto.

[0057] The cobalt (Co)-containing raw material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or oxyhydroxide, and may specifically be Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O or a combination thereof, but the present invention is not limited thereto.

[0058] The manganese (Mn)-containing raw material may be, for example, manganese-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides, oxyhydroxides or a combination thereof, and may specifically be: manganese oxides such as Mn2O3, MnO2 and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate and fatty acid manganese salts; manganese oxyhydroxide, manganese chloride or a combination thereof, but the present invention is not limited thereto.

[0059] The transition metal-containing solution can be prepared by adding a nickel (Ni)-containing raw material, a cobalt (Co)-containing raw material and a manganese (Mn)-containing raw material to a solvent (specifically water or a mixture of water and an organic solvent that can be uniformly mixed with water (such as alcohol, etc.)), or by mixing an aqueous solution of a nickel (Ni)-containing raw material, an aqueous solution of a cobalt (Co)-containing raw material and a manganese (Mn)-containing raw material.

[0060] The aluminum-containing solution contains sodium aluminate (NaAlO2) as an aluminum (Al)-containing raw material. During the coprecipitation reaction, sodium aluminate (NaAlO2) forms AlO(OH) instead of Al(OH)3. Because AlO(OH) has a different steric effect from Al(OH)3, when sodium aluminate is used as an Al-containing raw material during the preparation of a precursor, grains are formed in a form in which the (001) plane is arranged in a direction that is not parallel to the long axis direction of the primary particle, specifically in a direction having an angle of 20° to 160° relative to the long axis direction of the primary particle.

[0061] The ammonium solution as a complexing agent may include, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3 or a combination thereof, but the present invention is not limited thereto. The ammonium solution may be used in the form of an aqueous solution, and, in this case, as a solvent, water or a mixture of water and an organic solvent (particularly alcohol, etc.) that can be uniformly mixed with water may be used.

[0062] The alkaline solution as a precipitant may include: an alkali metal or alkaline earth metal hydroxide such as NaOH, KOH or Ca(OH)2; a hydrate thereof; or a combination thereof. The alkaline solution may also be used in the form of an aqueous solution, and in this case, as a solvent, water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that can be uniformly mixed with water may be used.

[0063] The alkaline compound is added in order to adjust the pH of the reaction solution, wherein the alkaline solution may be added in an amount such that the pH of the metal solution is within a range of 11 to 13.

[0064] The coprecipitation reaction may be performed in an inert atmosphere such as nitrogen or argon at a temperature ranging from 40°C to 70°C.

[0065] The transition metal hydroxide particles such as nickel-cobalt-manganese-aluminum hydroxide particles of the present invention having a specific orientation are formed by the above method and precipitated in the reaction solution. The precipitated transition metal hydroxide particles can be separated and dried according to a conventional method to obtain a positive electrode active material precursor.

[0066] <Positive Electrode Active Material>

[0067] Furthermore, the present invention provides a cathode active material prepared by using the cathode active material precursor according to the present invention.

[0068] Specifically, the positive electrode active material may be prepared through the steps of mixing a positive electrode active material precursor with a lithium source and sintering the mixture to form a lithium transition metal oxide.

[0069] As a lithium source, lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide or oxyhydroxide can be used, and there is no particular limitation on these materials as long as they can be dissolved in water. Specifically, the lithium source can be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi or Li3C6H5O7, and any one thereof or a mixture of two or more thereof can be used.

[0070] The positive active material precursor and the lithium source may be mixed and sintered at 730° C. to 830° C. to form a lithium transition metal oxide. Preferably, the sintering may be performed at 750° C. to 810° C., for example, 780° C. to 800° C., and the sintering may be performed for 5 to 20 hours, for example, 8 to 15 hours.

[0071] If necessary, further doping elements M may be mixed during sintering. 1 Raw materials. 1 For example, it may be at least one selected from the following: zirconium (Zr), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P) and sulfur (S), and the doping element M 1 The raw material may contain M 1 acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide or a combination thereof. During sintering, M 1 In the case of 1 The element diffuses into the lithium transition metal oxide and is doped by sintering, so the effect of improving the structural stability of the positive electrode active material can be obtained.

[0072] The positive electrode active material of the present invention thus prepared is a positive electrode active material in the form of secondary particles in which multiple primary particles are aggregated, wherein the long axis of the primary particle is arranged in a direction from the center of the secondary particle toward its surface, wherein the primary particle may contain grains in which the (003) plane is arranged in a direction having an angle of 20° to 160°, for example, 40° to 140°, relative to the long axis direction of the primary particle.

[0073] In the positive electrode active material of the present invention, the major axis of the primary particle is arranged in a direction from the center of the secondary particle toward its surface, and in this case, the primary particle may be columnar. Because lithium ions move along the interface between the primary particles in the positive electrode active material particles, when the primary particles are arranged in a direction from the center of the secondary particle toward its surface, the movement path of lithium is shortened compared to the case where the primary particles are randomly arranged, thereby improving the mobility of lithium.

[0074] The (001) plane of the positive electrode active material precursor is converted into the (003) plane of the positive electrode active material by sintering, wherein the insertion / deinsertion of lithium ions in the (003) plane is impossible. Thus, when the area of ​​the (003) plane exposed to the lithium migration path is large, the capacity characteristics and output characteristics are deteriorated.

[0075] However, since the positive electrode active material of the present invention is prepared by using a positive electrode active material precursor in which the (001) plane is arranged at an angle of 20° to 160°, for example, 40° to 140°, relative to the long axis direction of the primary particle, the (003) planes in the grains of the positive electrode active material are arranged in a direction having an angle of 20° to 160°, for example, 40° to 140°, relative to the long axis direction of the primary particle.

[0076] Therefore, since the area of ​​the (003) plane in which intercalation / deintercalation of lithium is impossible exposed under the surface of the primary particle is minimized, the cathode active material of the present invention exhibits excellent capacity, charge and discharge efficiency, and output characteristics.

[0077] Figure 3 FIG. 2 shows a positive electrode active material according to an embodiment of the present invention, wherein the short arrow in the figure indicates the arrangement direction of the (003) plane. Figure 3 It can be confirmed that the (003) plane of the cathode active material of the present invention is arranged in a direction not parallel to the long axis direction of the primary particle, specifically, arranged in a direction having an angle of 20° to 160° or 40° to 140° relative to the long axis direction.

[0078] The positive electrode active material of the present invention may be composed of a lithium transition metal oxide containing nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). Preferably, the lithium transition metal oxide may contain aluminum (Al) at a concentration of 1 mol% or more, for example, 1 mol% to 10 mol%, relative to all metal elements other than lithium. In the case of containing aluminum (Al) within the above concentration range, the formation of cation disorder and oxygen vacancies can be suppressed, thereby improving the life characteristics and resistance increase rate characteristics.

[0079] Aluminum (Al) can be contained in the secondary particles of the positive electrode active material without a concentration gradient. Since aluminum (Al) is uniformly distributed in the secondary particles without a concentration gradient, the agglomeration of aluminum (Al) can be suppressed, thereby minimizing the decrease in capacity and improving the effect of using a small amount of aluminum (Al) to improve the life characteristics and resistance increase rate characteristics.

[0080] The positive electrode active material according to the present invention may be a lithium transition metal oxide represented by the following [Formula 2].

[0081] [Formula 2]

[0082] Li a [Ni x1 Co y1 Mn z1 Al s1 ] 1-b M 1b O2

[0083] In Formula 2,

[0084] a represents the molar ratio of lithium to transition metal in the lithium transition metal oxide, where a can satisfy 0.8 ≤ a ≤ 1.2, 0.9 ≤ a ≤ 1.2, or 0.9 ≤ a ≤ 1.1.

[0085] x1 represents the molar ratio of nickel relative to all transition metal elements in the lithium transition metal oxide, where x1 can satisfy 0.7 ≤ x1 ≤ 0.99, 0.8 ≤ x1 ≤ 0.99, 0.85 ≤ x1 ≤ 0.99, or 0.88 ≤ x1 ≤ 0.99.

[0086] y1 represents the molar ratio of cobalt relative to all transition metal elements in the lithium transition metal oxide, where y1 can satisfy 0 < y1 < 0.3, 0 < y1 < 0.2, 0 < y1 < 0.15, or 0 < y1 < 0.12.

[0087] z1 represents the molar ratio of manganese relative to all transition metal elements in the lithium transition metal oxide, where z1 can satisfy 0 < z1 < 0.3, 0 < z1 < 0.2, 0 < z1 < 0.15, or 0 < z1 < 0.12.

[0088] s1 represents the molar ratio of aluminum relative to all transition metal elements in the lithium transition metal oxide, where s1 can satisfy 0.01 ≤ s1 ≤ 0.1, 0.01 ≤ s1 ≤ 0.08, or 0.01 ≤ s1 ≤ 0.05.

[0089] M 1 is a doping element doped in the lithium transition metal oxide, and can be, for example, at least one selected from the following: Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.

[0090] b represents the molar ratio of the doping element M that replaces the transition metal site in the lithium transition metal oxide 1 where b can satisfy 0 ≤ b ≤ 0.1 or 0 ≤ b ≤ 0.05.

[0091] <Positive Electrode and Lithium Secondary Battery>

[0092] According to another embodiment of the present invention, a positive electrode for a secondary battery and a lithium secondary battery are provided, and the positive electrode for the secondary battery and the lithium secondary battery include the positive electrode active material prepared as described above.

[0093] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on the positive electrode current collector and including the positive electrode active material.

[0094] In the positive electrode, there is no particular limitation on the positive electrode collector as long as it has conductivity without causing adverse chemical changes in the battery, and for example: stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the thickness of the positive electrode collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the collector to improve the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, etc.

[0095] Furthermore, the positive electrode active material layer may further contain a conductive material and a binder in addition to the above-mentioned positive electrode active material.

[0096] In this case, the conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the conductive material can be: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powder or fiber of metals such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof can be used. The content of the conductive material is generally 1% to 30% by weight based on the total weight of the positive electrode active material layer.

[0097] In addition, the binder improves the adhesion between the positive active material particles and the adhesion between the positive active material and the collector. Specific examples of the binder can be: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the total weight of the positive active material layer, the content of the binder can be 1% by weight to 30% by weight.

[0098] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a typical method for preparing a positive electrode. Specifically, a positive electrode material mixture containing the above-mentioned positive electrode active material and a selective binder and a conductive material can be applied to a positive electrode collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode collector. In this case, the type and amount of the positive electrode active material, the binder and the conductive material are the same as those previously described.

[0099] The solvent may be a commonly used solvent in the art. The solvent may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one thereof or a mixture of two or more thereof may be used. If the coating thickness and manufacturing yield of the slurry are taken into account, the solvent may dissolve or disperse the positive electrode active material, the conductive material and the binder, and may be such that a viscosity having excellent thickness uniformity may be provided during subsequent coating for preparing the positive electrode is sufficient.

[0100] Furthermore, as another method, the positive electrode may be prepared by casting the positive electrode material mixture on a separate support and then laminating a film separated from the support on a positive electrode current collector.

[0101] According to another embodiment of the present invention, an electrochemical device comprising the positive electrode is provided. The electrochemical device may be specifically a battery or a capacitor, for example, a lithium secondary battery.

[0102] The lithium secondary battery specifically comprises a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. In addition, the lithium secondary battery may also selectively comprise a battery container for accommodating an electrode assembly of the positive electrode, the negative electrode and the separator, and a sealing member for sealing the battery container.

[0103] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0104] There is no particular limitation on the negative electrode collector as long as it has high conductivity without causing adverse chemical changes in the battery, and for example: copper, stainless steel, aluminum, nickel, titanium, calcined carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; and aluminum-cadmium alloy. In addition, the negative electrode collector may generally have a thickness of 3 μm to 500 μm, and similar to the positive electrode collector, fine concavoconvexities may be formed on the surface of the collector to improve the adhesion of the negative electrode active material. For example, the negative electrode collector may be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, and the like.

[0105] In addition to the negative electrode active material, the negative electrode active material layer also selectively contains a binder and a conductive material. The negative electrode active material layer can be prepared by coating a negative electrode material mixture containing the negative electrode active material and optionally a binder and a conductive material on a negative electrode current collector and drying the coated negative electrode current collector, or by casting the negative electrode material mixture on a separate support and then laminating a film separated from the support on the negative electrode current collector.

[0106] Compounds that can reversibly intercalate and deintercalate lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials can be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds that can form alloys with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; metal oxides that can be doped and undoped with lithium such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a metal compound and a carbonaceous material such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon may be soft carbon and hard carbon, and typical examples of high-crystalline carbon may be irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch, and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.

[0107] Furthermore, the binder and the conductive material may be the same as those previously described in the positive electrode.

[0108] In a lithium secondary battery, the separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transfer of electrolyte ions can be used. Specifically, a porous polymer film, such as a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a laminated structure having two or more layers thereof can be used. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be selectively used.

[0109] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.

[0110] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0111] As an organic solvent, any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. In these solvents, carbonate solvents can be used, for example, a mixture of a cyclic carbonate (such as ethylene carbonate or propylene carbonate) and a low-viscosity straight-chain carbonate compound (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) that can improve the charge / discharge performance of the battery with high ionic conductivity and high dielectric constant can be used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.

[0112] Lithium salts can be used without particular limitation, as long as they are compounds that can provide lithium ions used in lithium secondary batteries. Specifically, the following substances can be used as lithium salts: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. Lithium salts can be used in a concentration range of 0.1M to 2.0M. In the case where the concentration of the lithium salt is included in the above range, since the electrolyte can have appropriate conductivity and viscosity, the excellent performance of the electrolyte can be obtained, and the lithium ions can be effectively moved.

[0113] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the electrolyte components, at least one additive may be added to the electrolyte, such as a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0114] As described above, since the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, the lithium secondary battery is suitable for: portable devices such as mobile phones, notebook computers and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).

[0115] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit battery and a battery pack including the battery module are provided.

[0116] The battery module or the battery pack may be used as a power source for at least one of the following medium and large-sized devices: a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0117] Example

[0118] Hereinafter, examples of the present invention will be described in detail in a manner that can be easily implemented by those skilled in the art. However, the present invention can be embodied in many different forms and should not be construed as being limited to the examples set forth herein.

[0119] Example 1

[0120] After 4 liters of distilled water were placed in a reactor (capacity 20 L), the temperature was maintained at 58 ° C, a transition metal aqueous solution of 2.29 mol / L NiSO4, CoSO4 and MnSO4 was mixed in an amount such that the molar ratio of nickel: cobalt: manganese was 88:5:7 and a solution of 0.291 mol / L NaAlO2 dissolved in a sodium hydroxide solution was added to the reactor at a speed of 500 ml / hour and 100 ml / hour, respectively, and a 9 wt % ammonia solution was continuously added to the reactor at a speed of 510 ml / hour. In addition, a 15 wt % sodium hydroxide aqueous solution was added at a speed of 206 ml / hour, and the addition amount of the sodium hydroxide aqueous solution was adjusted so that the pH was maintained at 11.7.

[0121] In the first 30 minutes, nucleation was performed while stirring at 600 rpm, and then the particles were grown while stirring at 250 rpm to 600 rpm. When the inside of the batch reactor was filled by performing the coprecipitation reaction for 20 hours, the stirring was stopped to precipitate the precursor particles, and after removing the supernatant and leaving 4 L of the reactant, the reaction was performed again. The reaction was performed for a total of 40 hours to form the precursor particles. The precursor particles were separated, washed in water, dried in a warm air dryer at 130°C for more than 12 hours, crushed and sieved to prepare the positive electrode active material precursor Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 (OH)2.

[0122] Example 2

[0123] The positive electrode active material precursor prepared in Example 1, LiOH and ZrO2 were mixed in an amount such that the molar ratio of Ni+Co+Mn+Al:Li:Zr was 1:1.07:0.0015, and sintered at 790°C for 10 hours in an oxygen atmosphere to prepare a positive electrode active material Li[Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 ] 0.9985 Zr 0.0015 O2.

[0124] Comparative Example 1

[0125] After 4 liters of distilled water were placed in a reactor (capacity 20 L), the temperature was maintained at 58° C., a transition metal aqueous solution of 2.29 mol / L in which NiSO 4 , CoSO 4 and MnSO 4 were mixed in an amount such that the molar ratio of nickel: cobalt: manganese was 88:5:7 was added to the reactor at a rate of 510 ml / hour, and a 9 wt % ammonia aqueous solution was continuously added to the reactor at a rate of 680 ml / hour. In addition, a 15 wt % sodium hydroxide aqueous solution was added at a rate of 612 ml / hour, and the amount of sodium hydroxide aqueous solution added was adjusted so that the pH was maintained at 11.6.

[0126] In the first 30 minutes, nucleation was performed while stirring at 600 rpm, and then the particles were grown while stirring at 250 rpm to 600 rpm. When the inside of the batch reactor was filled by performing the coprecipitation reaction for 20 hours, the stirring was stopped to precipitate the precursor particles, and after removing the supernatant and leaving 4 L of the reactant, the reaction was performed again. The reaction was performed for a total of 40 hours to form the precursor particles. The precursor particles were separated, washed in water, dried in a warm air dryer at 130°C for more than 12 hours, crushed and sieved to prepare the positive electrode active material precursor Ni 0.88 Co 0.05 Mn 0.07 (OH)2.

[0127] Comparative Example 2

[0128] After 4 liters of distilled water were placed in a reactor (capacity 20 L), the temperature was maintained at 58 ° C, a transition metal aqueous solution of 2.29 mol / L NiSO4, CoSO4 and MnSO4 mixed in an amount such that the molar ratio of nickel: cobalt: manganese was 88:5:7 and a 1.145 mol / L Al(NO3)3 aqueous solution was added to the reactor at a rate of 500 ml / hour and 20 ml / hour, respectively, and a 9 wt % ammonia aqueous solution was continuously added to the reactor at a rate of 510 ml / hour. In addition, a 15 wt % sodium hydroxide aqueous solution was added at a rate of 306 ml / hour, and the amount of sodium hydroxide aqueous solution added was adjusted so that the pH was maintained at 11.4.

[0129] In the first 30 minutes, nucleation was performed while stirring at 600 rpm, and then the particles were grown while stirring at 250 rpm to 600 rpm. When the inside of the batch reactor was filled by performing the coprecipitation reaction for 20 hours, the stirring was stopped to precipitate the precursor particles, and after removing the supernatant and leaving 4 L of the reactant, the reaction was performed again. The reaction was performed for a total of 40 hours to form the precursor particles. The precursor particles were separated, washed in water, dried in a warm air dryer at 130°C for more than 12 hours, crushed and sieved to prepare the positive electrode active material precursor Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 (OH)2.

[0130] Comparative Example 3

[0131] The positive electrode active material precursor prepared in Comparative Example 1, LiOH, Al2O3 and ZrO2 were mixed in an amount such that the molar ratio of Ni+Co+Mn:Li:Al:Zr was 1:1.07:0.02:0.0015, and sintered at 770°C for 10 hours in an oxygen atmosphere to prepare a positive electrode active material Li[Ni 0.88 Co 0.05 Mn 0.07 ] 0.9785 Al 0.02 Zr 0.0015 O2.

[0132] Comparative Example 4

[0133] The positive electrode active material precursor prepared in Comparative Example 2, LiOH and ZrO2 were mixed in an amount such that the molar ratio of Ni+Co+Mn+Al:Li:Zr was 1:1.07:0.0015, and sintered at 790°C for 10 hours in an oxygen atmosphere to prepare a positive electrode active material Li[Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 ] 0.9985 Zr 0.0015 O2.

[0134] [Experimental Example 1: Crystal Orientation Identification]

[0135] The positive electrode active material precursor of Example 1 was subjected to transmission electron microscopy (TEM) analysis, and the angle between the long axis of the primary particle and the (001) plane was confirmed by the FAST Fourier transform (FFT) pattern of the high-resolution image. The cross-sectional TEM image of the positive electrode active material precursor prepared in Example 1 is shown in Figure 4 As a result of confirming the FFT pattern of the high-resolution image, it was confirmed that the angle formed by the (001) plane and the major axis of the primary particle in the positive electrode active material precursor of Example 1 was 54°.

[0136] In addition, cross-sectional STEM analysis was performed on the positive electrode active material of Example 2 and the positive electrode active material of Comparative Example 4, and the angle between the major axis of the primary particle and the (003) plane was confirmed by selected area diffraction pattern (SADP).

[0137] Figure 1 FIG. 4 is a cross-sectional STEM image of the positive electrode active material prepared in Comparative Example 4, and the arrow in the figure indicates the direction of the (003) plane. Figure 1As shown, it can be confirmed that the positive electrode active material of Comparative Example 4 has a radial arrangement structure in which the long axis of the columnar primary particles is arranged from the center of the secondary particles toward the surface direction. In addition, as a result of confirmation by SADP, it can be confirmed that the (003) plane grows in a direction parallel to the long axis direction of the primary particles in the positive electrode active material of Comparative Example 4.

[0138] Figure 3 : is a cross-sectional STEM image of the positive electrode active material prepared in Example 2, and in the figure, the short arrow indicates the direction of the (003) plane, and the long arrow indicates the long axis direction of the primary particle. Figure 3 As shown, it can be confirmed that the positive electrode active material of Example 2 has a radial arrangement structure in which the long axis of the columnar primary particles is arranged from the center of the secondary particles toward the surface. In addition, as a result of confirmation by SADP, in the positive electrode active material of Example 2, the angle formed by the (003) plane and the long axis of the primary particle is 54°.

[0139] [Experimental Example 2: Capacity and Output Characteristics]

[0140] The various positive electrode active materials prepared in Example 2 and Comparative Examples 3 and 4, carbon black conductive materials and PVdF binder were mixed in an N-methylpyrrolidone solvent in a weight ratio of 96:2:2 to prepare a positive electrode material mixture, and one surface of an aluminum current collector was coated with the positive electrode material mixture, dried at 100°C, and then rolled to prepare a positive electrode.

[0141] Lithium metal was used as the negative electrode.

[0142] Various lithium secondary batteries were prepared by preparing an electrode assembly by placing a porous polyethylene separator between the positive electrode and the negative electrode prepared as described above, placing the electrode assembly in a shell, and then injecting an electrolyte into the shell. In this case, the electrolyte was prepared by dissolving 1.0M lithium hexafluorophosphate (LiPF6) in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (mixed volume ratio of EC / EMC / DEC = 3 / 4 / 3).

[0143] The various lithium secondary battery half cells prepared as described above were charged to 4.25V at 25°C at a constant current of 1C and terminated at 3C. Thereafter, the various lithium secondary battery half cells were discharged to a voltage of 3.0V at a constant current of 0.1C to evaluate the capacity, efficiency and output characteristics. The results are shown in Tables 1 and Figure 5 middle.

[0144] [Table 1]

[0145]

[0146] Referring to Table 1, the measured capacity or efficiency of the positive electrode active material of Example 2 is the best, and, as Figure 5 As shown, the room temperature output characteristics of Example 2 are also significantly better.

Claims

1. A cathode active material precursor for a secondary battery, the cathode active material precursor being in the form of secondary particles in which a plurality of primary particles are aggregated, wherein the major axis of the primary particle is arranged in a direction from the center of the secondary particle toward the surface thereof, wherein the primary particle comprises a crystal grain in which a (001) plane is arranged in a direction having an angle of 20° to 160° with respect to a major axis direction of the primary particle, The positive electrode active material precursor is a hydroxide containing nickel, cobalt, manganese and aluminum. 2 . The positive electrode active material precursor for a secondary battery according to claim 1 , wherein the primary particle comprises crystal grains in which the (001) plane is arranged in a direction having an angle of 40° to 140° with respect to a long axis direction of the primary particle. 3 . The cathode active material precursor for a secondary battery according to claim 1 , wherein the cathode active material precursor contains aluminum at a concentration of 1 mol % or more relative to all metal elements. 4 . The cathode active material precursor for a secondary battery according to claim 1 , wherein the cathode active material precursor contains aluminum at a concentration of 1 mol % to 10 mol % relative to all metal elements. 5 . The cathode active material precursor for a secondary battery according to claim 1 , wherein an aspect ratio of the primary particles is in the range of 3 to 15. 6 . The cathode active material precursor for a secondary battery according to claim 1 , wherein the aluminum is contained at a constant concentration in the secondary particles.

7. The positive electrode active material precursor for a secondary battery according to claim 1, wherein the positive electrode active material precursor is represented by Formula 1: [Formula 1] No x1 What y1 Mn z1 Al s1 (OH)2 in, In formula 1, 0.7≤x1≤0.99,0 <y1<0.3,0<z1<0.3,0.01≤s1≤0.1。 8. A method for preparing the positive electrode active material precursor for a secondary battery according to claim 1, the method comprising: While adding a transition metal-containing solution containing cations of nickel, cobalt and manganese, an aluminum-containing solution containing cations of aluminum, an alkaline aqueous solution and an ammonium solution to a reactor, a positive electrode active material precursor is formed by a coprecipitation reaction, The aluminum-containing solution comprises sodium aluminate.

9. The method of claim 8, wherein the sodium aluminate is co-precipitated to form AlO(OH).

10. A method for preparing a positive electrode active material for a secondary battery, the method comprising: Mixing the positive electrode active material precursor according to claim 1 with a lithium source, and The mixture is sintered to form a lithium transition metal oxide.

11. A positive electrode active material for a secondary battery, the positive electrode active material being in the form of secondary particles in which a plurality of primary particles are aggregated, wherein the major axis of the primary particle is arranged in a direction from the center of the secondary particle toward the surface thereof, wherein the primary particle comprises a crystal grain in which a (003) plane is arranged in a direction having an angle of 20° to 160° with respect to a major axis direction of the primary particle, The positive electrode active material is a lithium transition metal oxide containing nickel, cobalt, manganese and aluminum. 12 . The cathode active material for a secondary battery according to claim 11 , wherein the primary particle comprises crystal grains in which the (003) plane is arranged in a direction having an angle of 40° to 140° with respect to a long axis direction of the primary particle. 13 . A positive electrode for a secondary battery, comprising the positive electrode active material according to claim 11 . 14 . A lithium secondary battery comprising the positive electrode according to claim 13 .

Citation Information

Patent Citations

  • Display device

    KR1020200010701A

  • Precursor of positive electrode active material for secondary battery and positive electrode active material prepared using same

    CN108701827A